Optimasi Pemberian Lumpur Aktif dan Dolomit dalam Pengolahan Limbah Cair Pabrik Kelapa Sawit - Widayanti, Erni; Subiantoro, Rijadi; Parapasan, Yonathan (Politeknik Negeri Lampung, 2018)
The palm oil mill effluent (POME) generally has very high of BOD and COD contents, so it must be processed before it is drained to the body water. The purpose of this research was to determine the capability of active sludge and dolomite rate and the combination both of them in reducing the palm oil industry liquid waste. This research was conducted in December 2016 until January 2017 at Chemical Analysis Laboratory, State Polytechnic of Lampung. This research consists of two factors. First factor was the use of active sludge (without active sludge and 1 kg of active sludge), and the second factor was dolomite rate (0,3%, 0,6%, and 0,9% dolomite).The results obtained were calculated bassed on average repetitions then at compared with the value of initial analysis and quality standard, but the COD value is calculated based on the percentage of the reduction value, and all the observed values are presented in the graph. The results showed that the 1 kg active sludge treatment was more effective in degrading the wastewater than with no active sludge. The increased dose of dolomite to 0.9% combined with 1 kg of active sludge will be followed by an increase in pH (6,23) and DO (0,26 mg.l-1), but decrease COD to 53,7%, TSS to 810 mg.l-1, turbidity value to 700 NTU, and potassium content to 4865 mg.l-1. Keywords: chemical oxygen demand, dissolved oxygen, palm oil mill effluent, total suspended solid, turbidity